2005
DOI: 10.1094/pd-89-1067
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Dispersal of the Oak Wilt Fungus by Colopterus truncatus and Carpophilus sayi in Minnesota

Abstract: Sap beetles (Nitidulidae) are considered important overland vectors of the oak wilt pathogen, Ceratocystis fagacearum, in the north central United States. Colopterus truncatus and Carpophilus sayi are thought to be the principal sap beetle vectors in Minnesota. Field studies using windoriented funnel traps baited with aggregation pheromones of the insects were conducted during 2 years in east central Minnesota. The studies compared temporal flight dynamics of Colopterus truncatus and Carpophilus sayi from Apri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 14 publications
2
4
0
Order By: Relevance
“…The results of this study were parallel to those reported by Ambourn et al . (2005) in the oak wilt disease鈥恠ap beetle system.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The results of this study were parallel to those reported by Ambourn et al . (2005) in the oak wilt disease鈥恠ap beetle system.…”
Section: Discussionsupporting
confidence: 92%
“…The results of this study were parallel to those reported by Ambourn et al (2005) in the oak wilt disease-sap beetle system. Ambourn et al (2005) reported that sap beetles associated with the disease posed the greatest risk to healthy oak stands when their contamination rates were higher in the spring. Similarly, in the pitch canker pathosystem, both beetle contamination rate and propagule load were higher in the spring and early summer, and therefore the risk of fungal transmission may be greatest during this period of the year.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These findings support the continued use of aerial surveys for P. ramorum in Oregon's forested landscapes. Investigation of the relative importance of multiple putative insect vectors of Ceratocystis fagacearum (the oak wilt fungus), a long-established pathogen, led to the conclusion that a nitidulid beetle is the principle vector species of oak wilt (Ambourn et al 2005;Juzwik et al 2004), whereas the smaller oak bark beetle (Pseudopityophthorus minutissimus) is minimally important in pathogen transmission in Minnesota (Ambourn et al 2006). Frequencies of pathogen-contaminated nitidulid beetles (Colopterus truncatus and Carpophilus sayi) present in freshly made wounds, and the nearly immediate arrival of C. truncatus to such wounds, have fostered greater adherence for following guidelines for removing recently wilted red oaks (sanitation), disposing of diseased material, and developing harvesting guidelines to reduce the potential for new infections via insect transmission.…”
Section: Invasive Pathogens Of Treesmentioning
confidence: 99%
“…A sap beetle contaminated with a single ascospore mass of C. fagacearum could have been blown into the southern United States, but would have needed to visit a fresh wound on a susceptible oak in order to establish the pathogen. The probability of any of these insect-mediated events happening is extremely low based on what is known about the frequency of contaminated insect dispersal within non-oak wilt stands within the range of oak wilt (3).…”
Section: Possible Pathway Of Introduction To the United Statesmentioning
confidence: 99%